Penggunaan Ayat-ayat Al-Qur’an dalam Ritual Pencak Silat Sigantang di Nagari Rura Patontang - Ahsan, Beni; Wirman, Eka Putra; Faizin, Faizin (Lembaga Yasin AlSys, 2024)
Every religious-based college definitely uses verses from the Koran as guidance and beliefs that must be carried out, as well as the Sigantang pencak silat college in Nagari Rura Patontang uses selected verses in every ritual of Sigantang silat activities. Either with a predetermined verse read before practice. This ritual practice is carried out by Pencak Silat Sigantang in Nagari Rura Patontang as a means of getting closer to Allah and the Koran through this ritual. This research uses qualitative research. The research approach uses observation, interviews and documentation methods. This research is based on field research, namely explaining and exploring clear conditions and phenomena regarding the situation that occurred. This research reveals symptoms as a whole through collecting data from naturalistic settings, using the researcher himself as the main or key instrument. Sigantang Pencak Silat is a cultural tradition that has been preserved to this day and has had many social and divine influences that have had a positive impact on society. This tradition is always presented for social purposes in the general public or society. This tradition also encourages people to be close to the Koran and to Allah because silat uses holy verses from the Koran. The verses used are 1. Al-Fatihah, 2. Ayat Kursi, 3. Al-Iklas, 4. Al-Falaq, 5. An-Nass. In pencak silat, the influence of reading the Koran is very important, including calming the soul, controlling emotions, and protecting oneself from various enemy attacks. Then the views of teachers and students regarding pencak silat can be said to be the same. Namely, they agree that pencak silat is the practice of people who practice and are required to use the reading of the holy verses of the Koran.